filmov
tv
Prove that `(tanA + secA-1)/(tanA -secA + 1)=(1 + sin)/cos A`
![preview_player](https://i.ytimg.com/vi/RmQ-c1HGhcM/maxresdefault.jpg)
Показать описание
prove that tana/seca-1+tana/seca+1=2coseca
Prove that tanA/secA-1+tanA/secA+1=2cosecA
Prove that : (tanA + secA - 1)(tanA + secA + 1) = 2sinA/(1 - sinA)
25. Prove that (tanA + secA-1)upon(tanA-secA+1)= (1+sinA)upon cosA = secA + tan A
Prove that `(tanA + secA-1)/(tanA -secA + 1)=(1 + sin)/cos A`
tanA+secA-1/tanA-secA+1=1+sinA/cosA|| tanA+secA-1/tanA-secA+1=1+sinA/cosA=cosA/1-sinA ||Trigonometry
10th.. prove that tanA+secA-1/tanA-secA+1 = 1+sinA/cosA
Prove that: (1+tanA-secA)×(1+tanA+secA)=2 tanA. TRIGONOMETRY @khajaacademymathematica1729
Show that tana+seca-1/tana-seca+1= cosa/1-sina
`(tanA+secA-1)/(tanA-secA+1)=(1+sinA)/(cosA)`
Prove that (TanA + SecA - 1) ÷ (TanA - SecA +1) = (1 + SinA) ÷ CosA
Prove that ( 1+ cotA - cosecA) ( 1+ tanA - secA) = 2
Prove that (TanA + SecA -1)/(TanA - SecA + 1) = (1 + SinA)/CosA | Class 10 Math | Trigonometry |
Prove that (tanA +sinA)/(tanA-sinA) = (secA +1)/(secA-1)
20: Trigonometry: Prove that tanA/(secA-1)= (tanA+secA+1)/(tanA+secA-1)
(tanA+SecA-1)/(tanA-SecA+1)=(1+SinA)/cosA(@ComfortUrMaths_PritiSingh )
Prove that: tanA/1-cotA + cotA/1-tanA = 1+secA.cosecA. | Class 10
Prove that SecA(1- SinA)(SecA + TanA)=1
Prove that: 1/secA+tanA=1-sinA/cosA trigonometry solved
Prove: `(secA+tanA-1)(secA-tanA+1)=2tanA`
Prove that seca+tana-1/tana-seca+1=cosa/1-sina | prove that tana+seca-1/tana-seca+1=cosa/1-sina |
(secA-tanA+1)/(1+secA+tanA) = (1-sinA)/cosA || Step by step Proof || Trigonometry||
Simplify secA (1 - sinA) (secA + tanA)
Prove that : tanA + sinA / tanA - sinA = secA + 1 / secA - 1.
Комментарии